Implementasi Revolusi Industri (4.0) Pada Ukm Ayam Broiler Melalui Mesin Pakan Ayam Otomatis Berbasis Internet Of Things (IoT) - Raup Padillah (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Small and medium enterprise (SME) of boiler chicken own by Mr Sugiran, had been pionered since 2015 was one of SME in Desa Jambewangi Banyuwangi that has been operationally effected by the corona virus desease. Some government policies on Corona desease in preventing the virus spread made this small bussiness threathen out of bussiness. Layoffs made by the company caused on the threatment and feeding process of the livestock that made mortality on the livestock were rising. The fall of chicken livestock prices made this bussiness threaten to be bankruptcy. As a result of problem identification faced by the partner, offered solution by team is by implementing technology on automatic chicken feeding base on internet of things (IoT) and its applied on pos franchise system. The result of using this application are rising on chicken livestock, decreasing in livestock mortality till harvesting period, economically cut the cost of feeding process, rising on income (omzet) for the partner in harvesting period of broiler chicken.